2022
DOI: 10.1186/s12960-022-00724-1
|View full text |Cite
|
Sign up to set email alerts
|

Health care workers’ experiences during the COVID-19 pandemic: a scoping review

Abstract: Background COVID-19 has challenged health systems worldwide, especially the health workforce, a pillar crucial for health systems resilience. Therefore, strengthening health system resilience can be informed by analyzing health care workers’ (HCWs) experiences and needs during pandemics. This review synthesizes qualitative studies published during the first year of the COVID-19 pandemic to identify factors affecting HCWs’ experiences and their support needs during the pandemic. This review was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
101
1
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(150 citation statements)
references
References 216 publications
16
101
1
4
Order By: Relevance
“…[26]. This reminds medical staff that when following up patients, in addition to repeatedly emphasizing the importance of medication compliance and improving bad lifestyles, they also need to inform patients that the development of the disease is controllable based on the medication prescribed by the doctor, to establish the confidence of patients in active treatment [27][28][29]. At the same time, patients should be encouraged to return to society and participate in more social activities to build a patient's psychological elastic support system and enhance the patient's ability to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…[26]. This reminds medical staff that when following up patients, in addition to repeatedly emphasizing the importance of medication compliance and improving bad lifestyles, they also need to inform patients that the development of the disease is controllable based on the medication prescribed by the doctor, to establish the confidence of patients in active treatment [27][28][29]. At the same time, patients should be encouraged to return to society and participate in more social activities to build a patient's psychological elastic support system and enhance the patient's ability to adapt.…”
Section: Discussionmentioning
confidence: 99%
“…Internationally, studies of healthcare workers have confirmed reactions of increased camaraderie and teamwork during the pandemic. 15 , 16 , 17 …”
Section: Discussionmentioning
confidence: 99%
“…Internationally, studies of healthcare workers have confirmed reactions of increased camaraderie and teamwork during the pandemic. [15][16][17] Rutger Bregman, in Human kind: A hopeful history 18 systematically tackles decades of research evidence and long-spouted truisms about individuals' lack of inherent goodness and desire to help one's fellow humans in times of crisis. From William Golding's premise in Lord of the Flies and the experience of populations bombed in WWII to Stanley Milgram's experiments, Bregman debunks them all and presents a convincing case for one of his central conclusions: 'when in doubt, assume the best' (p. 382).…”
Section: Unprofessional Behavioursmentioning
confidence: 99%
“…Various studies have found witnessing patients' experiences to be difficult for both nurses and physicians. 24,[44][45][46] Furthermore, becoming stressed and feeling helpless are dependent not only on personal characteristics, but also on the presence of situational factors that surround the death event. 47 Accordingly, healthcare managers should provide HCWs, especially females, with professional psychological counseling and guidance as a routine, rather than offering such services only when HCWs are seen to be mentally struggling.…”
Section: Dovepressmentioning
confidence: 99%